Blockchain para dinámicas replicadoras en tiempo discreto (2020)
The development of distributed control and optimization frameworks has brought new challenges in terms of security and resilience due to attacks to specific nodes in the system. On the other hand, blockchain and smart contracts have proven to be a suitable technology to ensure safe distributed systems such as cryptocurrency like Bitcoin and Ethereum. For these reasons, in this work we present a methodology for the use of distributed control and optimization methods in blockchain. In particular, we consider the framework of discrete time distributed population dynamics due to its attractive for several engineering applications and easy implementation.